2019
DOI: 10.1111/jop.12840
|View full text |Cite
|
Sign up to set email alerts
|

Association between geographic tongue and psoriasis: A systematic review and meta‐analyses

Abstract: Geographic tongue (GT) has been described as a predictor of psoriasis. The objective of this study was to analyse the prevalence of GT in psoriatic and non‐psoriatic patients. For this purpose, we conducted a systematic review and meta‐analysis. A literature search was performed on PubMed, Embase, Web of Science and the Cochrane Database of Systematic Reviews. The search and selection process was performed according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta‐Analyses) criteria. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
2
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(48 citation statements)
references
References 23 publications
2
28
2
16
Order By: Relevance
“…As there is evidence for a genetic background for both GT and psoriasis with well documented associations with susceptibility regions such as PSORS1, HLA antigens or with specific mutations such as in the IL36RN gene, one explanation might be differences in the genetic makeup of studied cohorts [28–31]. Corroborating this hypothesis, the percentage of healthy volunteers with GT in our study was also low (2.3 %) compared to other studies in which prevalence rates of GT in control groups ranged from 0.88 % to 9 % (mean = 5.2 %) [16]. Thus, it is conceivable that different prevalence rates of GT between ethnicities and geographic regions might lead to divergent results in studies on the association of GT with psoriasis [16, 19, 22].…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…As there is evidence for a genetic background for both GT and psoriasis with well documented associations with susceptibility regions such as PSORS1, HLA antigens or with specific mutations such as in the IL36RN gene, one explanation might be differences in the genetic makeup of studied cohorts [28–31]. Corroborating this hypothesis, the percentage of healthy volunteers with GT in our study was also low (2.3 %) compared to other studies in which prevalence rates of GT in control groups ranged from 0.88 % to 9 % (mean = 5.2 %) [16]. Thus, it is conceivable that different prevalence rates of GT between ethnicities and geographic regions might lead to divergent results in studies on the association of GT with psoriasis [16, 19, 22].…”
Section: Discussionsupporting
confidence: 50%
“…It has been published that GT and FT are associated with psoriasis [7, 9, 14, 16, 24, 26]. Furthermore, it has been speculated that GT, due to its histological resemblance with psoriasis, might constitute a form of “oral psoriasis”, a notion which has recently been supported by a meta‐analysis [16, 27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, 2/23 patients with GT reported that they suffered from psoriasis. In a recently published meta‐analysis, it was concluded from ten studies that there is a statistically significant association between the frequencies of GT and psoriasis (Gonzalez‐Alvarez, Garcia‐Martin, & Garcia‐Pola, ). However, it is not yet possible to draw the conclusion that some autoimmune factor is linked to the etiology of GT.…”
Section: Discussionmentioning
confidence: 99%